Bentuk Palaminan sebagai Interior Istano Basa Pagaruyuang - N, Ilfa Septiani; Bahrudin, Ahmad; Akbar, Taufik (Relief : Journal of Craft, 2024)
This research is entitled "The Shape of Palaminan as the Interior of Istano Basa Pagaruyung." Its purpose is to describe the form of application and what elements, in terms of motifs and colors, are found in the palaminan at Istano Basa Pagaruyung. This research uses a descriptive qualitative research method. The object of this research is Palaminan in Istano Basa Pagaruyung. Informants in this study were obtained using a purposive sampling method. This palaminan research method was conducted through qualitative research to describe the palaminans found in Istano Basa Pagaruyung. Data was collected through observation, interviews, documentation, and recording of the interview results. The results of Palaminan research in Istano Basa Paguruyung consist of nine elements in their application, there are 5 motifs and colors that give the value of Minangkabau traditionalism, seen in terms of aspects of color psychology. Palaminan color has a meaning that is compatible with the function of space utilization that applies Palaminan to the building in Istano Basa Paguruyung. Keywords: shape, palaminan, interior, Istana Basa Pagaruyuang